A Conflict Profile On The Rohingya Conflict in Myanmar - Mahmud, Md. Tareq (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
‘Rohingya’- world’s most persecuted minority group came to the attention of the international media again in the mid of 2017 due to the brutality they were experiencing in their homeland by the state authority of Myanmar. Now they are being labeled as the ‘perpetual other’ of Myanmar and as the ‘Bengali intruders’ by the society regardless of being the inhabitants in the Rakhine state for centuries (The Diplomat 2017). As a result of this Bangladesh experienced the largest surge of displaced people into its border after its independence. They are ‘culturally discriminated, economically exploited and politically sidelined’ and are being discerned by the Arakan people as a threat to their national identity and an additional competitor for the natural resources (Wolf 2015). It is widely believed that the reason of the violent crackdown of the military against the ‘Rohingya’ community in the Arakan state is either religiously or ethnically motivated. But this is only a splinter part of the entire truth. These violent atrocities against the Rohingya community is more politically and economically motivated than religiously and ethnically. This paper will focus on the causes of the present crisis which started to unveil since 2017 and how these are linked with the interest of the different stakeholders like: the Military junta of Myanmar, Arakan Rohingya Salvation Army (ARSA), ASEAN, Bangladesh, Indian government, China, the UN, etc. To understand the causes and the effects of the conflict this paper will use the tool of ‘conflict tree’ and the ‘conflict onion’ will be used as a tool to understand the positions, needs and interests of different actors.